Khirbet Kerak Ware (Kura-Araxes) Andirons at Tel Bet Yerah: Functional Analysis and Cultural Context. (2nd January 2019) - Ishoev, Sergey; Greenberg, Raphael
Abstract : Horseshoe-shaped andirons have long been viewed, on little evidence, as a stand-in for the fire installations that play a central role in houses associated with the Kura-Araxes cultural tradition. A detailed examination of more than 100 andiron fragments from Tel Bet Yerah, accompanied by structural analysis and computerized simulation, has provided primary forensic evidence on their use, breakage and discard, and insights on their relation to ceramic cooking and consumption vessels. Our analysis reveals a previously unreported component of food preparation and consumption practices in the south Levantine branch of the Kura-Araxes diaspora that offers a striking contrast to local south Levantine behaviours and traditions.